The Autonomy of Mathematical Knowledge : Hilbert's Program Revisited. - Franks, Curtis (Cambridge University Press, 2009)
This study reconstructs, analyses and re-evaluates the programme of influential mathematical thinker David Hilbert, presenting it in a new light.